ARTIFICIAL INTELLIGENCE (AI) AND ACTING TRAINING DELIVERY AND PRACTICE IN NIGERIA - Babalola , Oluyinka Smart; Adodo, Emmanuel Ohiosinmuan; Oyetoro Hafiz Adebimpe PhD, Oyetoro Hafiz Adebimpe (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
Artificial intelligence has gone mainstream and is already positively and positively impacting many professions. The effect of AI on the acting profession is expected to be far reaching with what has been observed in AI Deep Fake capability. While there have been various studies on AI and its impact on professions, scant attention has been paid to the effect of AI on acting training delivery and practice. Therefore, this paper is aimed at investigating ways to mainstream AI into acting training and practice in Nigeria to ensure its possible positive impact. Using descriptive research methods, the study interrogates the intersection of acting and AI through adaptation, innovation, and ethical consideration. This study finds that AI can be a very positive phenomenon in actor training and in the theatre and entertainment practice. The integration of AI into acting training and practice in Nigeria will present a fascinating connection between technological innovation and artistic expression, as it offers promising opportunities for actors and the entertainment industry. These prospects include AI-driven performance analysis, virtual rehearsals, and augmented reality performances that can revolutionize actor training, collaboration modes, and audience engagement. The study concludes that adapting to AI in acting training and practice requires deep collaboration between actors, directors, producers, AI developers, ethicists, and policymakers. Through this kind of innovative collaboration, the entertainment industry can harness the positive potential of AI while safeguarding the rights and well-being of all involved. Finally, the paper recommends that actor training and the profession should incorporate AI while upholding obligatory ethical principles and standards for the profession to continue to evolve and thrive in the digital age.